Water balance - lake water level from Feresjön, lake level - Asa Research Station (Swedish University of Agricultural Sciences, 2024)
Accurate measurements of the lake water level for the lakes in SITES Water.
Asa Research Station (2024). Water balance - lake water level from Feresjön, lake level, 2020-09-14–2024-10-02 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/nhs-XeKYxuIC8p-fnJIvwebA
Keywords: Asa Research Station; Lake levels; Lake/Pond; Time instant; Time instant; Lake level; Lake level; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap